Aspectos farmacológicos das novas norcucurbitacinas glicosídicas de wilbrandia (cf) verticillata - Almeida, Fernanda Regina de Castro (1989)
The purified fraction of the rhizome of Wilbrandia (cf) vertiçillata (cabeça de negro) that contained two novel norcucurbitacin glucosides and identified as Wv^ and WV2 was investigated for its possible anti-inflammatory, an tifertility, laxative and cytotoxic cffects. In mice, the LD^g values for the fraction by ip and oral routes wcre 345 1 11 and 975 1 99 mg/kg respecti vely while in KB cell lines, it demonstrated low cytotoxicity with an ED^g of 12 pg/ml. In rat models of inflammation, the fraction demonstrated significant (p < 0,05) anti-inflammatory activity. The carrageenan-induced paw edema was inhibited by 25,4 and 39,5% at doses of 100 and 200 mg/1<g respectively. At 100 mg/kg, carrageenan-induced granulomatous lesion was inhibited by 45,82% where as the formaldehyde-induced arth ritis was supressed on the tenth dav of observation by 63,42%. Besides, the capillary permeability induced by acetic acid in mice was effectively reduced in a dose depen dent manner. The reduction was 69,11 and 90,36% for the rejs pective doses of 50 and 100 mg/kg po. The fraction at an oral dose of 50mg/kg exhibited laxative property by promoting wet. faeces and its effect was comparable to 0,5 mg/kg of Isocucurbitacin B. xx xx i At 100 mg/kg po, the fraction prolonged the dies trus phase of the reproductive cycle in mice but this effect was however, found to be reversible upon discontinua tion of medication, thus suggesting a possible anti-ovulato ry activity of it. When administered orally to rats on davs 1 to 7 of pregnancy, it decreased the number of fetal implantations at doses of 100 and 200 mg/kg. The extent of de crease was 33,3 and 66,6% for the respective doses. At simi lar doses, the fraction did not exhibit any abortifacient pro perty, when treated on days 9-13 of pregnancy. At 200 mg/kg dose, it however, impaired fetal growth. The fraction (100 mg/kg po) was found to be devoid of either estrocjenic or antioestrogenic property in immature rats. In isolated rat uterus, the fraction (0,05-0,4 mg/ml) inhibited the contractile responses evoked by acetyl ______________________________ y choline (5,5 x 10 M), bradykinin (1,89 x 10 M), oxytocin * (2,98 x 10 12M), BaCl2 (1,5 x 10 ~M), serotonin (2,84 x -6 -4 10 M) and KC1O (1 x 10 M) in a concentraiion dependent manner. The order of inhibition for the different agonists was as follows: BRADYKININ OXYTOCIN ACETYLCHOLINE BaCl2> SEROTONIN. A tendency to overcome its inhibitory effect was however, observed when calcium concentration in the nutrient fluid was enhanced by 2 to 3 fold. In isolated toad rectus abdominis, the fraction produced concentration de- _7 pendent inhibition of acetylcholine (1,1 x 10 M) evoked responses but did not modify the contractile responses evo- -4 -2 ked by KC12 (4 x 10 M) and caffeine (3 x 10 M). The fraction produced no significant effect on histamine (3,45 x xxii 10 M) evoked contractile responses of isolated guinea-pig ileum. The possible mechanisms involvcd in the observed pharmacoloqical properties of the fraction were discussed in relation to known biochemical effects of cucurbitacins in general. The study provided a scientific validation of the traditional use of the rhizome of Wilbrandia (cf) verticillata in arthritis and related disorders and suggest that it may be a useful alternative to presently available anti-inflammatory drugs. The anti-implantation and antiovulatory effects observed in plant preparation treated animais merit further study to explore the possibility of developing an oral contraceptive drug of plant origin.